Length–weight relationship of three fish species from the Qiantang River, China. (13th December 2018) - Guo, Aihuan; Yuan, Julin; Lian, Qingping; Hao, Yabin; Zhang, Aiju; Gu, Zhimin
Summary: Length–weight relationships (LWRs) of the three fish species, Pseudobagrus albomarginatus (Rendahl, 1928), Pseudobagrus crassilabris  (Günther, 1864), and Rhinogobius davidi (Sauvage & Dabry de Thiersant, 1874), were determined respectively. Samples were collected from Qiantang River, China during March 2016–December 2017. The b values ranged from 2.525 to 2.917, the coefficient of determination ( r 2 ) ranged from 0.96 to 0.97. Prior to this study, the length–weight relationship for P. albomarginatus and R. davidi were unknown to FishBase and the new maximum total lengths for three species were not recorded in FishBase. These results are useful for the fishery research and management in Qiantang River.